Effect of humidity on electrical property of ECA joints for dual stage micro-actuator in hard disk drives applications - Tangwitmonai, Nussara; Aungkavattana, Pavadee; Bintachitt, Patamas (Asia-Pacific Journal of Science and Technology, 2017)
The conductivity of isotropic conductive adhesives (ICA) is the most important property for the ICA functionality. Good ICA must provide the high conductivity or lowel ectrical resistance. In this paper, the electrical resistance of two ICA types, polyimide based(ICA type I) andepoxy based(ICA type II) have been investigated under the humidexposure of 85 C/85% RH from 0 to 384 h. Inaddition, the degradation mechanisms of conductive adhesive joints were determined. The electrical resistances of both types of ICA joints increased as the exposure time ofthe humiditytest increased. After humidity testing, there was no signifiant structural change at the interfaces and in conductive adhesive area for both ICA types. However, it is likely that oxidation of copper observed by SEM/EDS causes an increase in electrical resistance. The metaloxidation is the dominant mechanism for the unstable electrical resistance phenomenon during high temperature andhigh humidity conditions.